Botulinum Toxin Type A in the Spasticity of Cerebral Palsy Related to Congenital Zika Syndrome: An Observational Study. (3rd April 2022) - Armani-Franceschi, Giulia; Luz, Cleber; Lucena, Pedro H.; d'Afonseca, Danilo; Sales, Henrique; Carvalho, Alessandra L.; Siqueira, Isadora C.; Silva, Karine; Portuense, Sandra; Monteiro, Larissa; Bandeira, Igor D.; Melo, Ailton; et al.
ABSTRACT: Purpose: Investigate the effect of botulinum toxin type-A (BoNT-A) on spasticity and motor performance in children with Cerebral Palsy (CP) related to Congenital Zika Syndrome (CZS). Methods: Prospective longitudinal observational study of 34 children with CP referred for BoNT-A treatment. Outcomes were evaluated with a muscle tone assessment scale (Modified Ashworth Scale – MAS) and the Patients' Global Impression of Improvement (PGI-I) scale. Results: Mean age was 32.06 ± 3.07 months and 85% were classified as Gross Motor Function Classification System (GMFCS) V. Primitive reflexes were present in 56% of the sample. The majority of the parents (97.9%) reported improvement in range of motion or reduction in spasticity after treatment with botulinum toxin. No side effects were recorded. When compared to the baseline, median reduction in the MAS was 0.5 (IQR = 0). Conclusions: The findings of this study suggest that BoNT-A may effectively promote functional improvements and reduce muscle tone, improving the child's and family's quality of life.